Respuesta :

Answer:

b= 2 is the solution for the given equation.

Step-by-step explanation:

Here, the given expression is:

[tex]\frac{7}{(b+3)}  + \frac{5}{(b-3)} = \frac{10b -2}{(b^{2} -9)}[/tex]

Simplifying Left side, we get

[tex]\frac{7}{(b+3)}  + \frac{5}{(b-3)}[/tex]

= [tex]\frac{7(b-3) + 5(b+3)}{(b+3)(b-3)}[/tex]

Also, by ALGEBARIC IDENTITY:[tex]x^{2} -y^{2} = (x+y)(x-y)[/tex]

So, [tex] (b+3)(b-3) = b^{2} -9 [/tex]

So, LHS becomes [tex]\frac{7(b-3) + 5(b+3)}{b^{2} -9}[/tex]

Compare both Left side, Right side we get

[tex]\frac{7(b-3) + 5(b+3)}{b^{2} -9}[/tex] =   [tex]\frac{10b -2}{(b^{2} -9)}[/tex]

or, 7(b-3) + 5(b+3) = 10b -2

⇒ 7b - 21 + 5b + 15 = 10b -2

or, 12b - 10b = 6-2

or, 2b = 4 ⇒ b = 4/2 = 2

b= 2 is the solution for the given equation.